Hubungan Tingkat Pendidikan, Pengetahuan Diet dan Masa Kerja Tenaga Distribusi Makanan Dengan Ketepatan Pemberian Diet Pasien Di RSUD RAA Soewondo Pati - Benowati, Rini, Endang Nur W. SST, Msi.,Med, Ahmad Farudin, SKM,M.Si (2016)
Introduction In Hospital the safety and satisfaction of the patients become the main priority in providing the health services. One of services in the hospital is food service of provide a right diet in order to help healing the process of a disease. The precision of diet for the patients is influence by several factors, including: education, knowledge, and tenure of the involved employees. Purpose To determine the relationship of education level, knowledge level on diet, tenure of the food distribution employees to the precision of diet for the patients in RSUD RAA Soewondo Pati. Research Method This is a descriptive analitical research using the cross sectional approach. 24 subjects were recruited and data were analyzed using chi square test. Results of the Research The study result shows that the majority of the employees' educational level was an advance education (87.5%), the majority of knowledge level was good (70.8%), and the majority of employees' tenure was long (75%). Statistic analysis shows that there was a relationship between the education level and the precision of providing diet (p : 0.000). However, relationship of and education to precision of providing diet was found. Conclusion there was a relationship between the knowledge level on diet and the precision of providing the diet to the patients. However there was no significant relationship between the education level and the precision of the patiens diet. There was also no relationship of the tenure and the precision in providing diet to the patiens.